Cross-cultural adaptation, reliability, and validity of the Persian version of the Lower Limb Functional Index. (December 2022) - khalilian-Ekrami, Noushin; Amirshakeri, Bahram; Ghanavati, Tabassom; Mokhtarinia, Hamid Reza; Gabel, Charles Philip
Abstract: Background: the Lower Limb Functional Index (LLFI) is a regional patient reported outcome measure (PROM) for evaluation of lower limb musculoskeletal functional status. No Persian-language (LLFI-Pr) version is available. Objectives: LLFI translation and cross-cultural adaptation to Persian and psychometric property evaluation. Study design: prospective diagnostic assessment. Methods: to establish the LLFI-Pr face and content validity, double forward-backward translation protocols were used plus cognitive interviews and the 'content validity index'(CVI). Psychometric properties were determined from a convenience sample (n = 307, age 47.18 ± 11.52 years, female = 58.3%) that concurrently completed the LLFI-Pr and Persian Lower Extremity Functional Scale (LEFS-Pr). Test-retest reliability (ICC2, 1, sub-sample, n = 64) was determined during a non-intervention period of 3–7 days. Internal consistency used Cronbach's Alpha (α), error used MDC90/95 from the SEM, and construct validity used Pearson's r between the LLFI-Pr and LEFS-Pr. Construct validity used exploratory factor analysis (EFA, suppression = 0.30) with non-Gaussian distribution protocols. Results: psychometric properties were high for test-retest reliability (ICC2, 1  = 0.90) and internal consistency (α = 0.77), moderate for construct validity (r = 0.63), with no floor or ceiling effects, error found SEM = 1.60, MDC90  = 3.7% and MDC95  = 4.42%. A two-factor (EFA) structure (total-variance = 22.01%), that consequently cannot be summated, was determined where five-items failed consistent factor-loading leaving a 20-item version with a high original-LLFI total-equivalency (r = 0.97). However, the general/region-specific item-ratio reduced from the recognized 60/40 ratio to 50/50. Conclusion: the 20-item LLFI-Pr is a valid two-factor solution with sound psychometric properties for research and clinical Persian-language populations with lower limb disorders. Highlights: The Lower Limb Functional Index (LLFI) is well suited to the Persian language context. The LLFI-Pr demonstrated high test-retest reliability and internal consistency. The LLFI-Pr showed moderate construct validity. The LLFI-Pr demonstrated two-factor structure as a 20-item PROM.